Novel evidence for an oncogenic role of microRNA-21 in colitis-associated colorectal cancer. Issue 9 (20th May 2015) - Shi, Chenzhang; Yang, Yongzhi; Xia, Yang; Okugawa, Yoshinaga; Yang, Jun; Liang, Yong; Chen, Hongqi; Zhang, Peng; Wang, Feng; Han, Huazhong; Wu, Wen; Gao, Renyuan; et al.
Abstract : Objective: miR-21 was found to be overexpressed in the colon tissues and serum of patients with UC and colorectal cancer (CRC); however, the exact roles of miR-21 in colitis-associated CRC remain unclear. The aim of our study was to investigate the biological mechanisms of miR-21 in colitis-associated colon cancer (CAC). Design: miR-21 expression was examined in the tumours of 62 patients with CRC from China and 37 colitis-associated neoplastic tissues from Japan and Austria. The biological functions of miR-21 were studied using a series of in vitro, in vivo and clinical approaches. Results: miR-21 levels were markedly upregulated in the tumours of 62 patients with CRC, 22 patients with CAC, and in a mouse model of CAC. Following azoxymethane and dextran sulfate sodium intervention, miR-21-knockout mice showed reduced expression of proinflammatory and procarcinogenic cytokines (interleukin (IL) 6, IL-23, IL-17A and IL-21) and a decrease in the size and number of tumours compared with the control mouse group. The absence of miR-21 resulted in the reduced expression of Ki67 and the attenuated proliferation of tumour cells with a simultaneous increase in E-cadherin and decrease in β-catenin and SOX9 in the tumours of CAC mice. Furthermore, the absence of miR-21 increased the expression of its target gene PDCD4 and subsequently modulated nuclear factor (NF)-κB activation. Meanwhile, miR-21 loss reduced STAT3 and Bcl-2 activation, causing an increase in the apoptosis of tumour cells in CAC mice. Conclusions: These observations provide novel evidence for miR-21 blockade to be a key strategy in reducing CAC.